Rethinking the "Gold Standard" of Racial Profiling: §287(g), Secure Communities and Racially Discrepant Police Power. (August 2019) - Coleman, Mat; Kocher, Austin
In this article, we explore methodological difficulties related to proving racial profiling, specifically in the context of §287(g) and Secure Communities enforcement. How it is that critical immigration researchers understand racial profiling as the object of their research, and how might they go about substantiating racial profiling in the field? Can racial profiling be made a straightforward object of problematization and, if not, why? We are particularly interested in how racial profiling can be so self-evidently at the core of programs like §287(g) and Secure Communities and yet how racialized law enforcement decisions and tactics are so often inscrutable—and difficult to prove—in the context of routine police work. Building on original fieldwork findings and data on roadblocks by §287(g) and Secure Communities agencies in central North Carolina, we dissect the differences between racially discrepant police work and racial profiling, and argue that chasing the "gold standard" of racial profiling risks leaving racially discrepant policing on the table as an apparently unproblematic, and perhaps even defensible, outcome of policing. As such, we argue that critical scholars should leave aside the problem of proving racial profiling and instead refocus on the problem of racially discrepant policing.